1991
DOI: 10.1002/path.1711650409
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the glomerular capillary area—a comparison of minimal change nephrotic syndrome, focal glomerular sclerosis, and pre‐eclampsia

Abstract: A morphometric analysis was performed to compare the capillary area in non-sclerotic glomeruli in focal glomerular sclerosis (FGS), pre-eclampsia with focal sclerotic change of the glomeruli, and minimal change nephrotic syndrome (MCNS). The mean and standard deviation of the capillary area was greater in FGS than in pre-eclampsia and MCNS. Tubulo-interstitial lesions, such as tubular atrophy, interstitial fibrosis, and lymphocytic infiltration, were more severe in FGS than in pre-eclampsia. The presence of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Using the morphometric analyses of Rumpelt et al [9]and Ishitobi et al [10], the microscopic images were recorded by a videocamera, then digitized and displayed on the computer monitor. For analysis, amyloid deposits on the arteriolar wall were encircled with the digital pen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the morphometric analyses of Rumpelt et al [9]and Ishitobi et al [10], the microscopic images were recorded by a videocamera, then digitized and displayed on the computer monitor. For analysis, amyloid deposits on the arteriolar wall were encircled with the digital pen.…”
Section: Methodsmentioning
confidence: 99%
“…We measured all cortical glomeruli in each visual field. The morphometric analysis of Rumpelt et al [9]and Ishitobi et al [10]were used for semiquantitative evaluation of the grade of pathological glomerular damage. The latter was determined based on staining of the sections with Congo red.…”
Section: Methodsmentioning
confidence: 99%
“…The glomerular capillary loop size was found to be significantly greater in progressive IgAN than in the non-CRF-IgAN group (1.37 times) or the controls (1.55 times). Ishitobi et al [13]found that pediatric patients with FSGS showed an average 1.4 times increase in the capillary loop area in comparison to minimal change nephrotic syndrome patients. The significant differences in the mean and standard deviation of the capillary loop area thus suggest that an unequal dilatation of these loops exists in IgAN and these glomeruli are also related strongly with progression.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that renal interstitial expansion caused by fibrosis destroys the tight structural and functional connection between the tubulus and peritubular capillaries. The obliteration of these capillaries leads to an increase in the resistance of the postglomerular capillary network and, therefore, to a rise in the intraglomerular pressure and, subsequently, to a dilatation of the glomerular capillaries in order to enlarge the glomerular tufts [13, 26]. We demonstrated a strong statistical correlation between A int and both glomerular tuft size (r 2 = 0.337, p < 0.001) and the glomerular capillary loop size (r 2 = 0.43, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation